Lipid biomarker-based verification of TB infection in mother’s and daughter’s mummified human remains (Vác Mummy Collection, 18th century, CE, Hungary) - Váradi, Orsolya A.; Szikossy, Ildikó; Spekker, Olga; Rakk, Dávid; Terhes, Gabriella; Urbán, Edit; Berthon, William; Pap, Ildikó; Maixner, Frank; Zink, Albert; Vágvölgyi, Csaba; Donoghue, Helen D.; et al. (Acta Biologica Szegediensis, 2021)
The perpetual burden of tuberculosis (TB) keeps drawing the focus of research on this disease. Among other risk factors (e.g., poor living conditions, malnutrition, smoking, HIV infection, etc.), being in close contact with a TB infected person requires special attention. For a better understanding of the disease, paleopathological investigations concerning TB have been carried out with various techniques for a long a time; nevertheless, analysis of incidence among family members is hardly possible in past populations. An exceptional group of naturally mummified individuals, the collection of the Vác mummies (Hungary, 18th century CE), is known about the large TB incidence rate, which has been revealed by aDNA analysis. Besides the high rate of TB infection, another interesting aspect of the collection is that in some cases, the family connections could be reconstructed. In this paper, we present the mycocerosic acid profiles gained by HPLC-HESI-MS measurements of two Vác mummies, who were mother and daughter according to the personal records. Earlier metagenomic analysis already revealed mixed M. tuberculosis infection with the same bacterial strains in both individuals; moreover, the same bacterial strains were recorded in both cases.